Factors Influencing Purchase Intention towards Dietary Supplement Products among Young Adults - Lee, Jia Hou; Lim, Kwoh Fronn; Yong, Kai Yun (2016)
This study aimed to explore the factors affecting young adults‟ purchase intention towards dietary supplement products. These factors included attitude towards consuming dietary supplements, subjective norms, perceived behavioral control, as well as demographic characteristics such as gender, income, and residential area. 300 respondents were equally recruited from the internet and also UTAR, Kampar campus to complete the questionnaire. Findings concluded that perceived behavioral control, subjective norms, and attitude significantly predicted the purchase intention of dietary supplement products. Among these variables, subjective norms was the strongest predictor. Besides that, demographic characteristic such as gender difference was found significant in purchase intention of dietary supplement products. In contrast, there was no significant difference found between types of residential area in purchase intention of dietary supplement products. A significant and positive relationship between income and purchase intention was discovered. The findings strengthened the Theory of Planned Behavior (TPB) of predicting purchase intention of dietary supplement products among young adults. Subjective norms, being the most significant predictor of purchase intention could also be constructive for marketers to effectively publicize dietary supplement use.